Polypoid Cystitis in a dog. A case report. - PAPADOPOULOS, NIKOLAOS KLEANTHI (Journal of the Hellenic Veterinary Medical Society, 2022)
ABSTRACT. Polypoid cystitis is a rare disease of younger male dogs. The aim of this article is to report an incidence of polypoid cystitis, which was observed in a dog. The 11-year-old dog had a 3-month history of hematuria. Upon surgical approach to the retroperitoneal area an irregularly thickened wall was revealed, and additionally six (6) cysts 1-6 mm in diameter protruded from the mucosal surface. Histological examination confirmed transitional cell hyperplasia covering a core of proliferating connective tissue, edema and a neutrophilic inflammatory cell infiltrate with areas of ulceration and hemorrhage. These lesions are consisted with polypoid cystitis which is is a rare-benign disease, histopathology is the means of definitive diagnosis and it is best treated with surgical cystotomy.